The determinants of financial literacy among micro, small, and medium-sized enterprise (MSMEs) in Bangladesh and Malaysia - Uddin, Mohammad Nazim; Nahar, Lutfun; Rahman, Mohammad Mizanur; Md Saad, Norma (Allied Business Academies, 2022)
Micro, small, and medium-sized enterprises (MSMEs) play an essential role in many countries' economic and social development. This sector, in particular, generates new job opportunities, encourages competition, and, as a result, boosts productivity. MSMEs' long-term viability is crucial. MSMEs often fail during the first five years of their existence. Poor money management is one of the reasons for this failure, primarily related to a lack of financial literacy. Financial literacy is also challenging regarding human resources' ability to accept funding from financial institutions. Consequently, this paper examines the extent of financial literacy among Grameen Bank and AIM MSMEs in six divisions throughout Bangladesh and Malaysia. A standardised questionnaire was used to collect data from 402 AIM and Grameen Bank MSMEs. The level of financial literacy among Grameen Bank and AIM MSMEs operators is investigated using descriptive and inferential analysis. As a result of the findings, structural equation modelling was used to determine how the components are linked, which significantly impacts financial literacy. According to the study, knowledge, socialisation, agents, attitude, awareness, and skills are significant predictors of financial literacy among AIM and Grameen Bank MSMEs operators in Bangladesh and Malaysia. Policymakers should consider how the characteristics and financial literacy skills of MSMEs affect their behaviour and actions in micro-entrepreneurship when they make decisions about how to help MSMEs get more money. This is particularly evident in Malaysia and Bangladesh.